Potent antimicrobial activity of hydrogel loaded with the antimicrobial peptide, D-Bac8c2,5 Leu, against monospecies and polymicrobial biofilms of Staphylococcus aureus and Pseudomonas aeruginosa - Shahrour, Hawraa; Ferreira, Daniela Alves; Sheridan, Luke; Fitzgerald-Hughes, Deirdre; O’Gara, James P.; Devocelle, Marc; Kelly, Helena; O’Neill, Eoghan (Frontiers in Microbiology, 2025)
IntroductionAcute and chronic wound infections involving biofilms and caused by antimicrobial resistant (AMR) pathogens present significant challenges in healthcare, leading to substantial patient morbidity, increased hospital stays, and rising healthcare costs. Novel antimicrobial therapies are urgently needed to address these infections.MethodsA screening of multiple antimicrobial peptides (AMPs) was performed and the most potent candidate, D-Bac8c2,5 Leu, was tested against monospecies and polymicrobial biofilms of Staphylococcus aureus and Pseudomonas aeruginosa using static and dynamic in vitro models. Cytotoxicity was evaluated on human cell lines, and the peptide was incorporated into a methylcellulose hydrogel to assess sustained release and antimicrobial efficacy as a hydrogel dressing.ResultsD-Bac8c2,5 Leu significantly reduced biofilm viability in both monospecies and polymicrobial biofilms. In static biofilm assays, treatment led to a 2–3 log reduction in bacterial load compared to untreated controls. In Duckworth biofilm flow device, a similar reduction was observed, demonstrating efficacy in conditions mimicking wound environments. Furthermore, D-Bac8c2,5 Leu exhibited low cytotoxicity against human cell lines, and its incorporation into a methylcellulose hydrogel facilitated sustained release and enhanced antimicrobial activity. Furthermore, the peptide-loaded hydrogel showed considerable efficacy in disrupting pre-formed biofilms, underscoring its potential as a novel treatment for acute and chronic wound infections.DiscussionThese findings highlight the potential of D-Bac8c2,5 Leu to help address the urgent need for effective therapies against AMR pathogens and biofilm-associated wound infections. Further studies should focus on in vivo efficacy to optimize its therapeutic application in wound care.